Revolutionary development of computer education : A success story - Nandasara, S. T. (2006)
The University of Colombo, Sri Lanka has been in the forefront of the “Computer Revolution” in Sri Lanka. It has introduced the teaching of computer programming and applications as early as in 1967, more than a decade before other educational institutions, thereby producing, over the years, a large number of pioneer computer scientists and IT graduates out of students entering the university from a variety of disciplines. They are presently employed as researchers, educators, data processing managers, analyst programmers, software engineers and in many others in the professional field of information technology, not only in Sri Lanka but also in other countries. Established in 1870 as the Ceylon Medical College by the government of that day under the leadership of Governor Sir Hercules Robinson, the University of Colombo could claim to have been associated with higher education for over 130 years. The University has become a center of excellence of international repute that contributes significantly towards national development and human resource development in the field on computer science and information communication technology, particularly in the South and South East Asian Region. This paper presents the milestones of the success story, which did not occur without a policy, plan, leadership, group work, collaboration, and donor support.